(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
The study is on the inventory of the tomato varieties cultivated in Kadawa area of Kano State from (1997-2017) as well as to identify the current most preferred variety by farmers and the reason for that. A survey design method was employed using questionnaire as the research instrument. About two hundred and eighty (280) respondents were selected from nine hundred and twenty-five (925) farmers using purposive sampling. The data collected were analyzed using frequency and percentage table. The result revealed that about 24 different tomato varieties were identified. Griffaton happened to be the most preferred variety by farmers of Kadawa. In Kadawa one out of every three farmers is cultivating Griffaton. This is because of its qualities that include high yield, durability, attractive sizes among others. All the tomato varieties the research identified to be cultivated in Kadawa are imported from abroad except technisem. This can be seen as a challenge to the home industries producing tomato seeds to be producing the product that can compete with those imported to be well accepted by farmers within and outside the nation. The paper advised the stakeholders to put more effort into providing qualitative and acceptable indigenous tomato varieties to avoid further extinction.